Endometrial Regenerative Cell-Derived Conditioned Medium Alleviates Experimental Colitis - Chenglu Sun; Jingpeng Hao; Hong Qin; Yanglin Zhu; Xiang Li; Baoren Zhang; Yafei Qin; Guangming Li; Hongda Wang; Hao Wang (Stem Cells International)
Background. Traditional interventions can play a certain role in attenuating ulcerative colitis (UC), known as one type of inflammatory bowel diseases, but sometimes are not effective. Endometrial regenerative cells (ERCs) have been shown to exert immunosuppressive effects in different models of inflammation, and stem cell-derived conditioned media (CM) have advantages over cell therapy in terms of easy access and direct action. However, whether ERC-CM could alleviate colitis remains unclear and will be explored in this study. Methods. Menstrual blood was collected from healthy female volunteers to obtain ERCs and ERC-CM. Acute colitis was induced by 3% dextran sodium sulfate (DSS), and ERC-CM was injected on days 4, 6, and 8, respectively, after induction. The disease activity index was calculated through the record of weight change, bleeding, and fecal viscosity during the treatment process. Histological features, macrophage and CD4+ T cell in the spleen and colon, and cytokine profiles in the sera and colon were measured. In addition, an in vitro lymphocyte proliferation assay was measured by using a CCK-8 kit in this study. Results. ERC-CM treatment significantly improved the symptoms and histological changes in colitis mice. ERC-CM increased the percentage of Tregs in the spleen and colon but decreased the percentages of M1 macrophages and Th1 and Th17 cells in the spleen and decreased the population of Th17 cells in the colon. In addition, ERC-CM treatment decreased the local expression of TNF-α, IL-6, and iNOS in the colon. Furthermore, ERC-CM increased the levels of anti-inflammatory cytokines IL-10 and IL-27 but decreased proinflammatory cytokines IL-6 and IL-17 in the sera. In addition, ERC-CM significantly inhibited ConA-induced mouse lymphocyte proliferation in vitro. Conclusion. The results suggest that ERC-CM can exert similar therapeutic effects as ERCs and could be explored for future application of cell-free therapy in the treatment of colitis.